Impact of Sports Recreation Programs to Develop Basketball Skills Among Preparatory Students - Hamed Ali Abdulhussein (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study aims to identify impact of a proposed recreational sports program on developing some basic basketball skills among preparatory students. The researcher used an experimental design with a single group and pre- and post-tests, as it was suitable for nature and objectives of study. Sample was selected purposively from preparatory school students, with main sample consisting of 16 students, in addition to a pilot sample of 12 students from study community outside main sample. The researcher used a set of skill tests to measure basic basketball skills, which included: zigzag dribbling test between cones, 30-second wall pass test, accurate pass to a specific target test, stationary shooting test, and ladder shot test, also prepared a proposed recreational sports program that lasted for 8 weeks, with 3 sessions per week, each session lasting 60 minutes, program included a set of games, competitions, and recreational activities related to basic basketball skills. Results showed statistically significant differences between pre- and post-tests for experimental group in all tests, skills under investigation are in favor of post-test, values are greater than tabulated (t) value at a significance level of 0.05, which indicates effectiveness of recreational sports program in improving skill performance level of students. It was recommended that use of recreational sports programs be expanded within physical education lessons because of their effective role in improving learning of sports skills and increasing students’ motivation to participate in sports activities.